5G physical layer : principles, models and technology components. - Zaidi, Ali; Athley, Fredrik; Medbo, Jonas; Gustavsson, Ulf; Durisi, Giuseppe; Chen, Xiaoming (Academic Press, 2018)
5G Physical Layer: Principles, Models and Technology Components explains fundamental physical layer design principles, models and components for the 5G new radio access technology - 5G New Radio (NR). The physical layer models include radio wave propagation and hardware impairments for the full range of frequencies considered for the 5G NR (up to 100 GHz). The physical layer technologies include flexible multi-carrier waveforms, advanced multi-antenna solutions, and channel coding schemes for a wide range of services, deployments, and frequencies envisioned for 5G and beyond. A MATLAB-based link level simulator is included to explore various design options.